1299. Epidemiology of Invasive Pneumococcal Disease (IPD) in the United States 2011-2019. (4th December 2021) - Gierke, Ryan; Farley, Monica M; Schaffner, William; Thomas, Ann; Reingold, Art; Harrison, Lee; Holtzman, Corinne; Burzlaff, Kari; Petit, Susan; Barnes, Meghan; Torres, Salina; Beall, Bernard; et al.
Abstract: Background: Thirteen-valent pneumococcal conjugate vaccine (PCV13) was recommended for U.S. children aged < 5 years in February 2010 and recommended in series with 23-valent pneumococcal polysaccharide vaccine (PPSV23) for adults aged ≥ 65 years in 2014. PCV13 has led to dramatic reductions in invasive pneumococcal disease (IPD) burden. New, higher valency PCVs (PCV15, PCV20) are expected to be licensed for adults in late 2021. We examined remaining PCV13-type IPD among children and adults and assessed IPD burden potentially preventable through PCV15 and PCV20 use. Methods: IPD cases (isolation of pneumococcus from sterile sites) were identified through CDC's Active Bacterial Core surveillance during 1998–2019. Isolates were serotyped by Quellung or whole genome sequencing. Incidence rates (cases/100, 000) were calculated using U.S. Census Bureau population denominators. Results: After introduction of PCV13 in children, by 2013–2014, PCV13-type IPD declined 89% (from 15 to 2 cases/100, 000) in children age < 5 years and 67% (from 19 to 7 cases/100, 000) in adults age ≥ 65 years. During 2014–2019, rates of PCV13-type IPD in children and adults remained stable. In 2018–2019, among children age < 5 years, serotypes 3, 19F, 19A, and 6C accounted for most of the remaining PCV13-type IPD (46%, 32%, 14% and 4% respectively) (Figure 1). Among adults age ≥ 65 years, serotypes 3, 6C, 19A, and 19F accounted for most of the remaining PCV13-type IPD (62%, 12%, 10%, and 9% respectively) (Figure 1). During 2015–2019, rates of PCV15 and PCV20-type IPD have remained stable. In 2018–2019, among adults age ≥ 65 years, PCV15 non-PCV13-type IPD rates were 3.6 cases per 100, 000 and accounted for 15% of all IPD. PCV20 non-PCV13-type IPD rates were 6.8 cases per 100, 000 and accounted for 29% of all IPD (Figure 2). Among children age < 5 years, PCV15 non-PCV13-type IPD rates were 1.6 cases per 100, 000 and accounted for 17% of all IPD. PCV20 non-PCV13-type IPD rates were 2.8 cases per 100, 000 and accounted for 39% of all IPD (Figure 2). Figure 1. Incidence rates of IPD among children < 5 years old, by pneumococcal conjugate vaccine type and individual PCV13 serotypes, 2011–2019 Figure 2. Incidence rates of IPD among adults ≥ 65 years old, by pneumococcal conjugate vaccine type and individual PCV13 serotypes, 2011–2019 Conclusion: Following the dramatic reductions after PCV13 introduction, PCV13-type IPD has remained stable during the past five years. There are opportunities to prevent an additional 30% IPD burden among adults through new PCV use. Disclosures: William Schaffner, MD, VBI Vaccines (Consultant) Lee Harrison, MD, GSK, Merck, Pfizer, Sanofi Pasteur (Consultant)